ACQUISITION OF BRAZILIAN RURAL LAND WITH FOREIGN PARTICIPATION: AN ANALYSIS OF MAIN LEGAL RESTRICTIONS, JURISPRUDENCE AND POSSIBLE ECONOMIC IMPACT DUE TO AGRIBUSINESS - Tamarindo, U. G. F.; Pigatto, G.; Braga Junior, S. S. (Revista Brasileira de Engenharia de Biossistemas, 2017)
The purchase of rural land, especially with the participation of foreigners in charge of Brazilian companies, is a controversial issue, mainly because it involves the debates about important economic strategies and, above all, national security and sovereignty. The issue is normative on federal laws 4.504/ 64, 5,709/71 and 6.634/79, as well as Decrees 74.965/74 and 85.064/80 and Normative Instruction No. 76/2013. However, after a number of interpretations on the subject, the Union General Advocacy directs the Brazilian government to maintain restrictions on the purchase of non-inclusive rural land to Brazilian companies, in which foreign legal entities that have a majority of their capital and reside or are headquartered abroad. Nevertheless, the doctrine and jurisprudence still diverge on the threshold of the limitations imposed by Law 5.709/71, and so, there is a scenario of legal uncertainty that has made the investments to be postponed and even directed to other countries of Latin America and Africa. Therefore, the objective of this paper is to characterize the legal requirements for the acquisition of Brazilian rural land with the participation of foreigners, as well as the current legal and jurisprudential scenario and, finally, to point out the possible direct economic impacts on agribusiness.